The Right to Property as a Dimension of the Right to Identity - Delgado Menéndez, María del Carmen (2009)
This article addresses the right to identity from a perspective linked to the right to property. The author argues that, at present, poor majorities do not have access to property, and are therefore excluded from effective legal protection of the right to property, and that this problem, in turn, prevents the right to identity of these majorities from being guaranteed. In this context, this contribution seeks to show how the right to property represents a crucial - and determining - factor for the effective safeguarding of the right to identity of persons. In this way, this paper focuses on a more inclusive perspective of the right to identity, extending its projection to the field of property rights and, above all, highlighting its relevance for the most vulnerable communities.